2021
DOI: 10.1177/00031348211032204
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality after Surgery—A Method to Decrease Pain After Surgery in Pediatric Patients

Abstract: Background Virtual Reality (VR) is used as an effective tool for distraction and as an adjunct for pain management. This study was conducted to compare VR to standard iPad use after surgery and examine its effect on pain score and opioid consumption. Methods This was a randomized controlled study, with stratification by surgery type, age group (7-12yo, 13-18yo) and gender. Pain and anxiety were assessed with validated scales (STAI, FACES, VAS, FLACC) and outcomes were compared between each group. Results 50 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 13 publications
(14 reference statements)
0
19
0
Order By: Relevance
“…While there is a rise in studies evaluating the use of VR for procedural anxiety and pain control, only a few studies have aimed to evaluate the use of VR after surgery . Specht et al performed a randomized clinical trial and found that VR was associated with reduced postoperative pain scores compared with tablet use among pediatric patients. Olbrecht et al also found VR to reduce pain and anxiety among pediatric patients after surgery.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…While there is a rise in studies evaluating the use of VR for procedural anxiety and pain control, only a few studies have aimed to evaluate the use of VR after surgery . Specht et al performed a randomized clinical trial and found that VR was associated with reduced postoperative pain scores compared with tablet use among pediatric patients. Olbrecht et al also found VR to reduce pain and anxiety among pediatric patients after surgery.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, there is a role for nonpharmacologic adjuncts to pain control. The application of VR in health care is steadily expanding, including procedural distraction, anxiety reduction, and pain control . One theory is that diversion of attention to pain through distraction may provide a slower response to pain signals .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one RCT examining digital intervention in breast cancer surgery patients, the treatment group showed significant reduction of time (by 5 days) toward cessation of opioid medications, as compared to the control group (digital health education) ( 13 ). In another RCTs, VR app intervention (as compared to standard iPad use) did not change postoperative pain scores nor opioid consumption in pediatric patients ( 50 ). As discussed below, with more ongoing RCTs studying digital interventions and opioid-based analgesia in pain patients, our results justify near-future SR/MA study to evaluate clinical efficacy of adjunct VR and mobile apps in conjunction with analgesics to improve pain management.…”
Section: Adjunct Digital Interventions For Opioid-based Analgesiamentioning
confidence: 94%
“…Two additional RCTs investigated digital interventions in pain patients taking opioid analgesics, but they did not meet all three inclusion criteria (the comparator was not pharmacological treatment alone) ( 13 , 50 ). In one RCT examining digital intervention in breast cancer surgery patients, the treatment group showed significant reduction of time (by 5 days) toward cessation of opioid medications, as compared to the control group (digital health education) ( 13 ).…”
Section: Adjunct Digital Interventions For Opioid-based Analgesiamentioning
confidence: 99%